Redox Biomarker Baseline Levels in Cattle Tissues and Their Relationships with Meat Quality - Zoi Skaperda; Angeliki Argyriadou; Paraskevi Maria Nechalioti; Maria Alvanou; Sotiria Makri; Efterpi Bouroutzika; Ioannis D. Kyriazis; Fotios Tekos; Aristidis S. Veskoukis; Theodoros Kallitsis; Robin Mesnage; Georgios Arsenos; et al. (MDPI AG, 2021)
Cattle breeds or crossbreds with high productivity traits have been developed to meet a growing demand for food. When intensive farming practices are followed, animals face several challenges which can result in poor performance, compromised welfare and the reduced quality of their products. Our study aims to highlight the resting values of the physiological oxidative stress that three cattle breeds exhibit, and their potential relationship with meat quality. For this purpose, we determined the levels of five common redox biomarkers (glutathione (GSH), catalase (CAT), total antioxidant capacity (TAC), thiobarbituric reactive substances (TBARS) and protein carbonyls (CARBS)) in the tissues of three commonly used beef cattle breeds (Charolais (CHA), Limousin (LIM) and Simmental (SIM)) and their association with specific meat quality traits that depend on color, pH and texture. The results revealed that LIM cattle breed animals have elevated intrinsic antioxidant defense systems in comparison to CHA and SIM cattle breed animals. In addition, the meat quality parameters were associated with the redox biomarkers. We propose that the determination of specific antioxidant parameters in the blood might be used as potential biomarkers to predict meat quality. This would allow farmers to nutritionally intervene to improve the quality of their products.